A brief discussion on the biological factors in the acquisition of language - Silva, Ronivaldo Braz da (Revista do GEL, 2007)
The understanding of how language is acquired and the role the brain plays in the language acquisition process are crucial because the development of language is one of the most important factcrs in human development. The analysis of language development is intrinsically connected with one’s awareness of how human beings or human brains perceive, learn, control, and coordinate elaborate behaviour. The study of language development, therefore, involves research on motor, perceptual, and cognitive development. This paper reviews the three major theories of language acquisition, namely, behaviouristic, psycholinguistic, and interactionistic and examines the biological component of language acquisition and the brain’s role in the language development process.